Pulmonary Kaposi sarcoma and disseminated Mycobacterium genavense infection in an HIV-infected patient - Tribuna, C (2016)
We report a case of Kaposi sarcoma (KS) and disseminated infection by Mycobacterium genavense in a 40-year-old HIV-positive man with CD4+ T-cell count 5/µL. He presented with anorexia, diarrhoea, cachexia and multiple firm violaceous nodules distributed over the face, neck and upper and lower extremities. Biopsy of a skin nodule was performed, confirming KS. Immunoperoxidase staining for human herpesvirus 8 was strongly positive. Endoscopic examination revealed erosive duodenopathy. Multiple biopsy samples showed numerous acid-fast bacilli at direct microscopic examination. Real-time PCR (RT-PCR) identified M. genavense. A CT scan showed diffuse pulmonary inﬁltrates with a 'tree-in-bud' appearance, striking splenomegaly and abdominal lymphadenopathy. A bronchoscopy was performed, revealing typical Kaposi's lesions in the upper respiratory tract. RT-PCR of bronchial aspirate identified M. genavense and Pneumocystis jirovecii. Despite treatment with highly active antiretroviral therapy, antimycobacterial therapy and trimethoprim/sulfamethoxazole, the outcome was fatal.